An Analysis of Factors Influencing the Timeliness of Annual Tax Return Filing at KPP Pratama Situbondo: A Qualitative Descriptive Approach - Blitzar Bimbi Prasetyo; Selvi Khoirun Nisa; Siti Nurhalizah; Ari Fahimatussyam Putra Nusantara (The Future of Education Journal, 2026)
This study aims to analyze the factors influencing the timeliness of Annual Tax Return filing among individual taxpayers (employees) at KPP Pratama Situbondo in the context of the implementation of the Core Tax Administration System (Coretax). The study employed a descriptive qualitative approach using the Technology Acceptance Model (TAM) framework, which includes perceived usefulness, perceived ease of use, attitude toward use, and behavioral intention to use. Data were collected through structured interviews and observations involving tax officers and individual taxpayers selected through purposive sampling. The findings indicate that the timeliness of Annual Tax Return filing is influenced by both internal and external factors. From the TAM perspective, perceived usefulness and perceived ease of use significantly affect taxpayers’ attitudes and intentions to use the system, which subsequently influence reporting behavior. However, several obstacles remain, including technical problems such as system errors and slow access, limited digital literacy, and difficulties in adapting to the new system. External factors, such as delays in receiving withholding tax documents, work-related busyness, geographical constraints, and perceptions of weak sanctions, also contribute to reporting delays. This study concludes that although Coretax has the potential to improve reporting efficiency, its effectiveness largely depends on user readiness, system reliability, and supporting infrastructure.